Chemical Derivatization Enables MALDI-TOF-Based High-Throughput Screening for Microbial Trimethylamine (TMA)-Lyase Inhibitors. (August 2019) - Winter, Martin; Bretschneider, Tom; Thamm, Sven; Kleiner, Carola; Grabowski, Daniel; Chandler, Sarah; Ries, Robert; Kley, Jörg T.; Fowler, Danielle; Bartlett, Christina; Binetti, Ralph; Broadwater, John; et al.
Microbial-dependent trimethylamine (TMA) generation from dietary precursors such as choline was recently linked to cardiovascular diseases (CVDs) as well as chronic kidney disease (CKD). Inhibition of TMA-generating enzymes in gut bacteria would be an innovative approach to treat these diseases. The potential to accurately quantify secreted TMA levels highlights the capacity of mass spectrometry (MS) for tracking microbial TMA-lyase activity. However, high-throughput screening (HTS) by conventional MS instrumentation is hampered by limited sample throughput. Recent advancement in liquid handling and instrumentation of matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS provides an HTS-compatible MS technology. The deciphering of enzymatic reactions using this label-free readout has been successfully applied but has thus far been limited to peptide/protein-centric activity assays. Here, we demonstrate the versatile applicability of MALDI-TOF by tracking a small molecule within a highly complex sample background. The key to success for this concept was chemical derivatization of the target molecule enabling quantitative assessment of microbial TMA formation. Further, its potential was demonstrated in a side-by-side comparison to RapidFire-MS in a primary screen and subsequent dose–response experiments. Overall, the established assay enables the screening for microbial TMA-lyase inhibitors and serves as a proof of concept for the applicability of MALDI-TOF for demanding assay concepts per se.